Implementation of the Education Quality of Pondok Al-Qur'an Al-Majidiyah Foundation Bagan BatuDistrict Rokan Hilir Regency - Syahrul Hasibuan; Wahyudin Nur Nasution; Junaidi Arsyad Arsyad (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to see and analyze the Implementation of the Quality of Education of the Al-Qur'an Al-Majidiyah Rokan Hilir Islamic Boarding School Foundation. The type of research is qualitative research, which is a form of research that naturally traces a phenomenon, so that objective conditions can be found. This research was conducted at the Al-Qur'an Al-Majidiyah Bagan Batu Islamic Boarding School Foundation, Bagan Sinembah District, Rokan Hilir Regency. The informants in this study were 7 people from the foundation, principal and also teachers and education personnel. The data collection techniques used were through interviews, observation and documentation. Meanwhile, the analysis used was Data Reduction, Data Presentation and drawing conclusions. The results of this study are the Planning of work programs to improve the quality of education through educator standards, namely educational qualification planning, equivalency and certification, competency training, supervision of educator performance, and Subject Teacher Deliberation (MGMP). Planning of standard facilities and infrastructure, namely planning to meet representative classrooms according to needs, supporting facilities and facilities for the teaching and learning process, and other supporting facilities such as sports fields, laboratories, offices and so on. The implementation of educator standards is through activities to improve educator qualifications, skills and competencies, professional development, monitoring and evaluating performance, conformity to values, and involvement in extracurricular activities and leadership. The implementation of standards for facilities and infrastructure to improve the learning environment, the welfare of students by providing good facilities, and the development of students' potential through the provision of facilities and infrastructure.